A study on awareness regarding preventive measures of worm infestation among the mothers group of Banepa municipality. - Shrestha, Sristi (2010)
ABSTRACT: A study on "Awareness Regarding Preventive Measures of Worm Infestation Among Mothers Group" was conducted in Banepa Municipality. The objective of this study was to assess the awareness regarding preventive measures of worm infestation. A descriptive cross sectional research design was used in total 100 samples using non probability snow ball sampling technique. Structured and semi- structured questionnaire consisting both open and close ended were used as the instrument for assessing the awareness regarding preventive measures of worm infestation. Data collection was done through the face to face interview technique. Split half method was used to test reliability of the instrument. Computer statistics, Statistical Package for the Social Sciences (SPSS 17.0) was used to analyze the computations. In this study, out of 100 respondents, majority were from 21- 25 age group. Threefourth (77%) was literate and one-fourth (23%) were illiterate. Majority of the respondent's children (84%) were not affected by worm infestation previously whereas (16%) of respondent's children were affected by worm infestation previously. The mean score of risk factor of worm infestation was 5.22, mean score of sign and symptoms was 7.36, mean score of modes of transmission was 4.30, and mean score of preventive measures was 8.37. The mean of total knowledge score of literate respondent was 25.81 with (S.D = 2.24) and illiterate mother was 23.3 with (S.D = 3.73). For hypothesis testing, independent t- test was used to test for significance at the confidence level of 95%, the obtained p value was 0.00 which revealed strongly statistically significant. This shows that literate mothers have more knowledge regarding preventive measures of worm infestation than illiterate mothers. Therefore, the awareness program regarding worm infestation should be encouraged in this area by conducting awareness program routinely and use of television, posters and pamplets should be considered to reach illiterate mothers.